The Immersed Boundary Method: Application to Two-Phase Immiscible Flows (Communications in Computational Physics, 2018)
In this paper we present an extended formulation of the immersed boundary(IB) method that facilitates simulation of incompressible immiscible two-phaseflows. In the developed formulation the pressure field and the surface tension forcesassociated with interface curvature are implicitly introduced in the form of distributedLagrange multipliers. The approach provides for impermeability between both phasesand exhibits accurate mass conservation without the need for additional correctionprocedures. Further, we present a grid independence study and extensive verificationof the developed method for representative 2D two-phase flows dominated by buoyancy,shear stress, and surface tension forces.
Keywords: Immersed boundary method; two-phase immiscible flow; distributed Lagrange multiplier.